Revolt! The Next Great Transformation from Kleptocracy Capitalism to Libertarian Socialism through Counter Ideology, Societal Education, & Direct Action. - Cavanaugh, Charles D. (Theory in Action, 2012)
The article reviews the book "Revolt! The Next Great Transformation from Kleptocracy Capitalism to Libertarian Socialism through Counter Ideology, Societal Education, & Direct Action," by John Asimakopoulos.